Strengthening Anti-Corruption Literacy Through Story Books Published by the Corruption Eradication Commission (KPK) for Elementary School Children at the Al Abna Islamic Boarding School in Brebes Regency - iqbal, muhamad (JUPE : Jurnal Pendidikan Mandala, 2025)
This study aims to strengthen anti-corruption values among elementary-aged children through the use of anti-corruption storybooks published by the Indonesian Corruption Eradication Commission (Komisi Pemberantasan Korupsi/KPK) at Al Abna Islamic Boarding School. The anti-corruption values examined include honesty, discipline, and responsibility. The research employed a Classroom Action Research (CAR) approach using the Kemmis and McTaggart model, conducted in two cycles consisting of planning, action, observation, and reflection stages. The research subjects were 15 elementary-aged students. The learning actions were implemented through storytelling activities, guided discussions, and story-based assignments using three KPK storybooks: Modo Tak Mau Menari, Piknik di Kumbinesia, and Suatu Hari di Museum Seni. Data were collected through behavioral observation sheets, teacher reflection notes, brief interviews, and documentation. Data analysis was conducted using descriptive qualitative analysis and simple quantitative techniques based on developmental categories: Not Yet Developed (BB), Beginning to Develop (MB), Developed as Expected (BSH), and Very Well Developed (BSB). The results showed a significant improvement in all three anti-corruption values. In the pre-cycle condition, most students were in the BB and MB categories. After the implementation of actions through Cycle II, more than 75% of students reached the BSH and BSB categories in honesty, discipline, and responsibility. These findings indicate that KPK anti-corruption storybooks are effective as character education media in Islamic boarding school settings and are able to promote positive behavioral changes among elementary-aged children.